Severe Panton–Valentine-Leukocidin-Positive Staphylococcus aureus Infections in Pediatric Age: A Case Report and a Literature Review - Valeria Garbo; Laura Venuti; Giovanni Boncori; Chiara Albano; Anna Condemi; Giuseppe Natoli; Valentina Frasca Polara; Sebastiano Billone; Laura Antonella Canduscio; Antonio Cascio; Claudia Colomba (Antibiotics)
Background: Infections caused by S. aureus strains encoding Panton–Valentine leukocidin (PVL-SA) have become increasingly relevant in community settings and can cause severe conditions in pediatric populations. We present the pediatric case of an invasive disease caused by PVL-SA and provide a literature review of severe manifestations caused by these strains in children. Methods: A PubMed search (February 2024) found studies that included relevant clinical outcomes, diagnostics, and treatments, excluding cases of asymptomatic infection or in adult populations. A logistical multivariate analysis was used to find predictors of the need for intensive care. Results: A 10-year-old boy came to the attention of our Pediatric Infectious Diseases Unit with fever, chest pain, and tachypnea. A rapid worsening of his clinical conditions was observed, with the development of necrotizing pneumonia, osteomyelitis, deep vein thrombosis (DVT), and multiple abscesses. Blood cultures confirmed the presence of PVL-producing methicillin-resistant S. aureus (MRSA). The initial treatment included linezolid and ceftaroline and was later adjusted to clindamycin, daptomycin, and fosfomycin, with clinical improvement. Discussion: Our review collected 36 articles, including 156 pediatric cases of severe PVL-SA infection. Bacteremia was present in 49% of cases, lung infection in 47%, and osteomyelitis in 37%. The presence of pulmonary localization was predictive of the need for intensive care, O.R. 25.35 (7.46–86.09; p < 0.001). Anti-toxin molecules were used in about half the cases where information on treatment was reported. Our report highlights the capacity of PVL-SA to cause life-threatening complications in children, while also discussing the full range of its clinical spectrum and the most effective therapeutic approaches.